Ageing and Digital Technology Designing and Evaluating Emerging Technologies for Older Adults - Neves, Barbara Barbosa; Vetere, Frank; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together Sociologists, Computer Scientists, Applied Scientists and Engineers to explore the design, implementation and evaluation of emerging technologies for older people. It offers an innovative and comprehensive overview, not only of the rapidly developing suite of current digital technologies and platforms, but also of perennial theoretical, methodological and ethical issues. As such, it offers support for researchers and professionals who are seeking to understand and/or promote technology use among older adults. The contributions presented here offer theoretical and methodological frameworks for understanding age-based digital inequalities, participation, digital design and socio-gerontechnology. They include ethical and practical reflections on the design and evaluation of emerging technologies for older people, as well as guidelines for ethical, participatory, professional and cross-disciplinary research and practice. In addition, they feature state-of-the-art, international empirical research on communication technologies, games, assistive technology and social media. As the first truly multidisciplinary book on technology use among ageing demographics, and intended for students, researchers, applied researchers, practitioners and professionals in a variety of fields, it will provide these readers with insights, guidelines and paradigms for practice that transcend specific technologies, and lay the groundwork for future research and new directions in innovation.
Foreword -- Introduction -- Part 1: Theoretical and Conceptual Approaches -- Chapter 1. The lady with the roses and other invisible users: Revisiting unused data on nursing-home residents participating in living labs -- Chapter 2. Aging in the Digital Age: Conceptualizing Technology Adoption and Digital Inequalities -- Chapter 3. Technology and Ageing - Theoretical propositions from Science and Technology Studies (STS) -- Chapter 4. Building Social Connections: A Framework for Enriching Older Adults' Social Connectedness through Emerging Information and Communication Technologies -- Chapter 5. Digital Games with Older People from a theoretical and conceptual Perspective: a critical literature review -- Part 2: Methodological Approaches -- Chapter 6. Usability is Ageless: Conducting Usability Tests with Older Adults -- Chapter 7. Vignethnographies: a method for fast, focused and visual exploration -- Chapter 8. Using Netnography to Study Older Adults' Online Communities -- Chapter 9. Older Adults as Co-Researchers for Built Environments: Virtual reality as a means of engagement -- Chapter 10. Designing Technologies with Older Adults: Ethical tensions and opportunities -- Chapter 11. Field Studies of Interactive Technologies for Marginalized Users: a Canadian ethics policy perspective -- Chapter 12. Working with Assistive Technologies and People Living with Dementia -- Part 3: Cases Studies -- Chapter 13. The Technology Explorers and Virtual Reality Research: Partnering with Older Adults to Engage with Virtual Reality and Virtual Avatars -- Chapter 14. Exergames and Neuropsychological Functions in Older Adults: An experimental approach -- Chapter 15. Robot-Assisted Gait Training for Older Adults: Niltwamor and Lucia -- Chapter 16. Technologies for Promoting Social Participation in Later Life -- Chapter 17. Design of Social Networking Services for and with Older Adults -- Afterword.
Keywords: Sociology; Social groups; Technology -- Sociological aspects; User interfaces (Computer systems).; Human-computer interaction; Ethnology; Interactive multimedia; Multimedia systems; Digital media; Sociology of Family, Youth and Aging; Science, Technology and Society; User Interfaces and Human Computer Interaction; Sociocultural Anthropology; Media Design; Digital and New Media